A conceptual model describing mechanisms for how yoga practice may support positive embodiment. Issue 4 (3rd July 2020) - Cox, Anne E.; Tylka, Tracy L.
ABSTRACT: Yoga practice has been associated with various indices of positive embodiment in correlational and intervention studies. Yet, systematic, theoretically-grounded models detailing specific mechanisms by which yoga supports positive embodiment are lacking. In this article, we present a conceptual model that describes mechanisms (i.e., mediators and moderators) that can be used to guide research to help answer how, for whom, and under what conditions yoga practice may promote positive embodiment. Based on existing theoretical frameworks and empirical findings, this model suggests that (a) yoga practice may cultivate embodying experiences during yoga (e.g., state mindfulness), (b) these embodying experiences may build stable embodying experiences that generalize beyond the yoga context (e.g., trait mindfulness), and (c) these stable embodying experiences may then promote embodying practices (e.g., mindful self-care). This mediational chain is likely moderated by the yoga context (e.g., instructional focus, presence of mirrors, diversity of bodies represented) and yoga practitioners' social identities (e.g., body size, physical limitations), social and personal histories (e.g., experiences with weight stigma and trauma), and personality traits and motives (e.g., body comparison, appearance-focused motives to practice yoga). Using the structure of this conceptual model, we offer researchers ideas for testable models and study designs that can support them.